2009
DOI: 10.1111/j.1551-2916.2009.03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Polymer‐Derived SiCN Materials as the Anode in Lithium Ion Batteries

Abstract: Polymer‐derived SiCN materials, pyrolyzed from polysilylethylenediamine at temperatures between 600° and 1500°C, are used as the anode in lithium batteries, and their electrochemical performance is studied. The SiCN materials, having composition ranging from organic to inorganic and phase structures from amorphous to crystalline, are obtained from pyrolysis at different temperatures. Electrochemical measurements show that the 1000°–1300°C derived SiCN materials exhibit a first‐cycle discharge capacity of 608–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…Depending on the scan rate the intercalation/extraction mechanism may be controlled by electron transfer (slow scan rate) or diffusion transport (high scan rate). If the redox process is controlled by diffusion, then the diffusion coefficient can be calculated from the modified Randles-Sevcik equation: /, = 2.69xl0 5 ■ n vi ■ S ■ D' /2 ■ c" · v ,/2 (4) where ¡ p is the peak current, n is the number of electrons per species reaction, S is the apparent surface area of the electrode (geometric area), D is the diffusion coefficient of Li + in the solid state and c* is the change in Li concentration in the material due to the specific step to which the peak is related. The Li concentration in graphite/SiCN composites was calculated using elemental analysis data of the C, N, O contents combined with electrochemical measurements according to equation (5) where xu = molar ratio of Li atoms in the host, Q rev = reversible capacity in mAh/g (galvanostatic charge/discharge with i = 18 mA/g), M mo \ -molecular mass of the host (100 g/mol), F = Faraday constant (96485 C/mol).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the scan rate the intercalation/extraction mechanism may be controlled by electron transfer (slow scan rate) or diffusion transport (high scan rate). If the redox process is controlled by diffusion, then the diffusion coefficient can be calculated from the modified Randles-Sevcik equation: /, = 2.69xl0 5 ■ n vi ■ S ■ D' /2 ■ c" · v ,/2 (4) where ¡ p is the peak current, n is the number of electrons per species reaction, S is the apparent surface area of the electrode (geometric area), D is the diffusion coefficient of Li + in the solid state and c* is the change in Li concentration in the material due to the specific step to which the peak is related. The Li concentration in graphite/SiCN composites was calculated using elemental analysis data of the C, N, O contents combined with electrochemical measurements according to equation (5) where xu = molar ratio of Li atoms in the host, Q rev = reversible capacity in mAh/g (galvanostatic charge/discharge with i = 18 mA/g), M mo \ -molecular mass of the host (100 g/mol), F = Faraday constant (96485 C/mol).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been a growing interest in SiCN polymer-derived ceramics (PDCs) as anode materials for lithium ion batteries [3,4]. We showed that polyvinylsilazane (PVS)-derived SiCN ceramics exhibit low discharge capacity (about 44 mAh/g) while the reversible capacity of graphite/polymer-derived SiCN composite is 10 times higher [3].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In spite of those promising results, the research on lithium storing in Si-based ceramics has been mostly dedicated to silicon oxycarbide (SiOC) materials while the lithium intercalation into SiCN-based ceramics has been Breviewed^first about 20 years later by Kolb et al [7], who studied lithium insertion into SiCN/graphite composites. Pure polymer-derived SiCN materials obtained from polysilylethylendiamine have been investigated by Su et al [8] and Feng [9]. The work of Su et al showed a first discharge cycle capacity of 456 mAh g −1 but the material suffered from strong fading with cycling.…”
Section: Introductionmentioning
confidence: 98%